Trends and Cost-Analysis of Lower Extremity Nerve Injury Using the National Inpatient Sample. Issue 2 (8th June 2018) - Foster, Chase H; Karsy, Michael; Jensen, Michael R; Guan, Jian; Eli, Ilyas; Mahan, Mark A
Abstract: BACKGROUND: Peripheral nerve injuries (PNIs) of the lower extremities have been assessed in small cohort studies; however, the actual incidence, national trends, comorbidities, and cost of care in lower extremity PNI are not defined. Lack of sufficient data limits discussion on national policies, payors, and other aspects fundamental to the delivery of care in the US. OBJECTIVE: To establish estimates of lower extremity PNIs incidence, associated diagnoses, and cost in the US using a comprehensive database with a minimum of a decade of data. METHODS: The National Inpatient Sample was utilized to evaluate International Classification of Disease codes for specific lower extremity PNIs (9560–9568) between 2001 and 2013. RESULTS: Lower extremity PNIs occurred with a mean incidence of 13.3 cases per million population annually, which declined minimally from 2001 to 2013. The mean ± SEM age was 41.6 ± 0.1 yr; 61.1% of patients were males. Most were admitted via the emergency department (56.0%). PNIs occurred to the sciatic (16.6%), femoral (10.7%), tibial (6.0%), peroneal (33.4%), multiple nerves (1.3%), and other (32.0%). Associated diagnoses included lower extremity fracture (13.4%), complications of care (11.2%), open wounds (10.3%), crush injury (9.7%), and other (7.2%). Associated procedures included tibial fixation (23.3%), closure of skin (20.1%), debridement of open fractures (15.4%), fixation of other bones (13.5%), and wound debridement (14.5%). The mean annual unadjusted compounded growth rate of charges was 8.8%. The mean ± SEM annual charge over the time period was $64 031.20 ± $421.10, which was associated with the number of procedure codes (β = 0.2), length of stay (β = 0.6), and year (β = 0.1) in a multivariable analysis ( P  = .0001). CONCLUSION: These data describe associations in the treatment of lower extremity PNIs, which are important for considering national policies, costs, research and the delivery of care.